Closed-Incision and Surrounding Soft Tissue Negative Pressure Dressings in Post-Mastectomy Pre-Pectoral Direct-to-Implant Breast Reconstruction: A Pilot Study. Issue 4 (November 2022) - Sibia, Udai S.; Singh, Devinder; Sidrow, Kathryn M.; Holton, Luther H.
Background: Closed-incision and surrounding soft tissue negative pressure therapy (cistNPT) is theorized to decrease infection, reduce tissue edema, and promote healing of the mastectomy skin flap. We report our early experience with this dressing in pre-pectoral direct-to-implant (pDTI) breast reconstruction.Methods: We retrospectively reviewed all patients who underwent post-mastectomy pDTI breast reconstruction with cistNPT between July 2019 and February 2020. All reconstructions utilized smooth round silicone gel implants and human acellular dermal matrix.Results: Thirty-five female patients underwent 58 mastectomies. Mean age and body mass index were 49.9 years and 28.9 kg/m 2, respectively. Eleven (31.4%) patients had neoadjuvant chemotherapy. The mean sternal notch-to-nipple distance was 27.0 cm. The median specimen weight was 483 g, while the median implant volume was 495 cc. The mean implant-to-specimen ratio was 1.4 for nipple-sparing, 1.1 for skin-sparing, and 0.7 for skin-reducing mastectomy. Total drain volume was 483.1 cc from each breast. Post-operative complications included seroma (5.2%), peri-incisional necrosis (8.6%), and superficial skin epidermolysis (13.8%). There were no cases of surgical site infection, dehiscence, or hematoma. Rate of return to the operative room was 3.4%. Mean follow-up was 90 days.Conclusions: In our series of pDTI breast reconstructions with cistNPT, no patients experienced hematoma, dehiscence, or infection complications. Rates of seroma, skin necrosis requiring operative debridement, and total drain volumes were lower than those reported in literature.